2015
DOI: 10.1074/jbc.m115.652545
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Interaction and Cytotoxicity of the Iowa Mutation of Apolipoprotein A-I (ApoA-IIowa) Amyloid Mediated by Sulfate Moieties of Heparan Sulfate

Abstract: Background:The G26R apolipoprotein A-I (apoA-I Iowa ) mutation causes familial amyloid polyneuropathy. Results: ApoA-I Iowa amyloid cellular interaction and cytotoxicity depended on cell surface heparan sulfate (HS). Enzymatic remodeling of HS by extracellular sulfatase mitigated cytotoxicity. Conclusion: Sulfate moieties of cell surface HS are critical for mediating apoA-I amyloid cytotoxicity. Significance: Enzymatic remodeling of HS may be a novel concept for regulating actions of amyloid on cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 63 publications
3
32
0
Order By: Relevance
“…It should be noted that no enhancing effect of heparin was observed on fibril formation by the 1-83/ G26R variant (Fig. 1B) despite the finding that apoA-I 1-83/G26R fibrils interact with cell surface HS [22]. This discrepancy might be because heparin interacts differently with the N-terminal fragment of apoA-I in the different aggregated states (monomer, oligomer, or fibrils).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It should be noted that no enhancing effect of heparin was observed on fibril formation by the 1-83/ G26R variant (Fig. 1B) despite the finding that apoA-I 1-83/G26R fibrils interact with cell surface HS [22]. This discrepancy might be because heparin interacts differently with the N-terminal fragment of apoA-I in the different aggregated states (monomer, oligomer, or fibrils).…”
Section: Discussionmentioning
confidence: 80%
“…In general, it is thought that HS and heparin work as a scaffold to facilitate protein aggregation through electrostatic interactions with a basic motif in the protein . Recently, we demonstrated that cellular interaction and cytotoxicity of apoA‐I G26R amyloid fibrils are mediated by cell surface HS . Since certain amyloidogenic mutations such as G26R place additional arginine residue into the N‐terminal aggregation prone regions of apoA‐I , it is expected that these mutations would affect the process of amyloid fibril formation by apoA‐I through interactions with GAGs.…”
mentioning
confidence: 99%
“…CHO cells are particularly suitable to this purpose and have been widely employed in SCFS applications (50,52,54,55). Furthermore, they have been also used as a model system to test protein aggregate toxicity (56)(57)(58), permitting a comparison of our data with those reported in the literature. The interaction between OA/OB species and the cell membrane was quantified as the mechanical work needed to detach a number of individual protein aggregate particles from the cell membrane.…”
Section: Introductionmentioning
confidence: 99%
“…30 Interestingly, the GAG heparan sulfate prevented cytotoxic interactions of the G26R (Iowa) mutant with CHO cells. 31 Thirdly, oxidation of methionine residues has been shown to accelerate fibril deposition at normal physiological pH. 27,28 Activated Page 4 of 40…”
mentioning
confidence: 99%